Optimum Microencapsulation Conditions of Lemongrass Essential Oil Microcapsule Using Complex Coacervation Method - Johan, Nur Ain Arina; Nasir, Siti Hana; Mohamed Rehan, Aisyah; Khadmudin, Dzulqarnain; Yahya, Mohamad Faizul (International Journal of Integrated Engineering, 2024)
Microencapsulation of essential oil provides new novelty applications in textile industries where the technology allows the addition of insect-repellent, thermoregulated, antibacterial or fragrance to all types of textile substrate. In this study, lemongrass essential oil (LEO) was microencapsulated using a complex coacervation technique. The effects of LEO formulations on particle diameter and encapsulation efficiency was investigated using Response Surface Methodology (RSM). Chitosan (CH) and Gum Arabic (GA) were used as wall materials, and the LEO microcapsules formulation was developed with 17 different formulations, using Design Expert 13.0 software. Each formulation parameters and its interaction significantly affect the response (p < 0.05). The mean particle diameter size of the produced LEO microcapsules was found ranging from 6 µm to 12 µm. and the encapsulation efficiency of LEO microcapsules varied between 78.59±0.01 to 85.32±0.56 %. The suggested optimal formulation condition by the predicted model was at 30g of LEO mass, 2g of CH mass, and 1g of GA mass with desirability of 0.982. This formulation are able to achieve a particle diameter of 12 µm and an encapsulation efficiency of 85.21 ± 0.06%.